IDENTIFIKASI HEWAN INVERTEBRATA PADA FILUM ANNELIDA DI DAERAH PENANGKARAN BUAYA ASAM KUMBANG DAN PANTAI PUTRA DELI - RAHMADINA RAHMADINA; LINDA ERIRI (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2018)
Annelids live in freshwater, sea and land water. Some are parasitic. Body symmetry is lateral symmetrical. The nervous system consists of a brain ganglion connected by a nerve cord that extends to form a rope ladder. The excretion device is called nephridium. Respiration using the epidermis on the entire surface of the body and takes place in diffusion. Closed circulatory system. Habitat earthworms live in burrows in moist, fertile soil and the temperature is not low. Annelida classification is based on the presence or absence after being divided into classes namely Polychaeta, Oligochaeta, and Hirudinea. Some types of Annelids are useful as food. Wawo and palolo worms can be used as a source of animal protein for humans, earthworms are useful for fertilizing agricultural land. Leeches can be used to clean pus on infected wounds. In addition, hirudin is useful in blood storage, which is for the purpose of blood transfusion.